Chromosomal Abnormalities in Infertile Men Referred to Iran Blood Transfusion Organization Research Center - F Mahjoubi; S Soleimani; S Mantegy (JRI, 2010)
Introduction: The prevalence of somatic chromosomal abnormalities in infertile male individuals has been reported to vary in different literatures. The aim of this study was to investigate the frequency of chromosomal aberrations among infertile men referred to the Cytogenetic Laboratory of Iran Blood Transfusion Organization Research Centre (IBTO). Materials and Methods: Chromosomal analysis was performed on phytohemagglutinin (PHA)-stimulated peripheral lymphocyte cultures of 1052 infertile men using standard cytogenetic methods. The study took place during 1997 to 2007. Results: Total chromosome alterations were revealed in 161 (15.30%) infertile men. The most prevalent chromosomal abnormality in the infertile men was 47, XXY, that was seen in 94 (58.38%) men while one of them had a mosaic karyotype: mos 47, XX[54]/47,XXY[18]/46,XY[9]. In 37 (22.98%) cases, structural aberrations were detected. There were 30 (18.63%) cases of sex reversal. Conclusion: Cytogenetic studies of these patients showed increased chromosomal abnormalities in infertile men in comparison with that of the normal population, justifying the need for cytogenetic analysis of men with idiopathic infertility.
Keywords: Chromosomal abnormalities, Cytogenetic, Infertility, Klinefelter’s syndrome, Male infertility, Sex reversal